The Influence of Academic Supervision and Pedagogical Competence on the Performance of Teachers at Guslah 4 Bangil Elementary School, Pasuruan Regency - Iva Faizah; Taufiq Harris; A. Faizin (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Teacher performance is a key determinant of successful teaching and learning processes and the achievement of educational quality. Previous studies have demonstrated that principals' academic supervision and teachers' pedagogical competence are two important factors contributing to improved teacher performance. However, the implementation of these factors in elementary schools within Cluster 4 Bangil, Pasuruan Regency, varies considerably, highlighting the need for empirical investigation into their influence on teacher performance. This study aims to examine the effects of academic supervision and pedagogical competence, both individually and simultaneously, on the performance of elementary school teachers. This study employed a quantitative approach using an ex post facto research design. The study population consisted of teachers from six elementary schools in Cluster 4 Bangil, Pasuruan Regency. A total of 54 teachers were selected using a total sampling technique. Data were collected through questionnaires that had met validity and reliability requirements and were analyzed using multiple linear regression preceded by classical assumption tests. The findings indicate that academic supervision has a positive and significant effect on teacher performance. Pedagogical competence also has a positive and significant effect on teacher performance. Furthermore, academic supervision and pedagogical competence simultaneously exert a significant influence on teacher performance. These findings suggest that continuous academic supervision, coupled with the strengthening of teachers' pedagogical competence, constitutes an essential strategy for enhancing the professionalism and performance of elementary school teachers.